A Study on Precedents of Employee Moonlighting Intention among Private School Teachers in Kanchipuram District - Mrs. Uthra.R, Dr.S.Nafeesa (International Journal of Advanced Science and Technology, 2020)
The HRM sphere experiences new ideas and concepts everyday due to growing labour supply and benchmarking. Moonlighting is a topic that is gaining momentum for research in India, even though moonlighting as such is not a new concept in India. The present study is conducted as a pilot study which tried to explore theA demographic profile of the moonlighting teachers in Kanchipuram district and the factors influencing their moonlighting intention. A questionnaire was circulated among 75 teaching faculty. The study found that the Financial needs play dominant role in determining moonlighting intentions of teachers.